Knowledge, attitude and awareness towards breast cancer among female nursing students in School of Health Sciences - Roslan, Mawwar Nadhirah (Pusat Pengajian Sains Kesihatan, 2020)
Breast cancer is one of the cancers that fearing entire women population in the world. As a healthcare professional, we need to ensure that they have a knowledge about breast cancer, attitude while facing the breast cancer and awareness towards breast cancer. Thus, a cross sectional, descriptive study was conducted on 188 respondents recruited using a simple random sampling method. A questionnaire that had been validated was given to all respondents that fit the inclusion criteria. The general objective of the study was to determine the knowledge, attitude and awareness towards breast cancer among female nursing students in School of Health Sciences (SHS), Universiti Sains Malaysia (USM). In this study, sociodemographic information of the respondents was analyzed using descriptive statistics. Not only that, descriptive statistics was also used to determine the level of knowledge, attitude and awareness towards breast cancer among female nursing students in SHS, USM. Besides, Pearson’s Chi-Square test was used to determine the association between the selected sociodemographic information on age with the level of knowledge towards breast cancer among female nursing students in SHS, USM. Then, Kruskal Wallis test was applied to determine the significant median difference between selected socio-demographic information on educational level with the level of knowledge towards breast cancer among female nursing students in SHS, USM. The findings of this study showed that majority of female nursing students in SHS, USM had good knowledge, positive attitude and higher awareness toward breast cancer. In this study, there is a statistically significant association between selected socio-demographic information on age with the level of knowledge towards breast cancer among female nursing students in SHS, USM (p<.002). There is a statistically significant difference of median total grade of knowledge towards breast cancer between educational status (year of study in university) which (p<.000). Increasing and enhancing the knowledge, attitude and awareness towards breast cancer among female nursing students will help them in giving health education towards the women and patient about the importance and understanding of breast cancer. Subsequently, they will be a competent and professional future nurses that can deliver a better care and treatment as well as improving the health and level of quality of life of the patients. It is recommended that each of the patients be more aware of their own health in preventing breast cancer from affecting their daily lives.